1999
DOI: 10.1103/physrevb.59.10928
|View full text |Cite
|
Sign up to set email alerts
|

Probing the single-wall carbon nanotube bundle: Raman scattering under high pressure

Abstract: We report experimental and theoretical investigations on the pressure dependence of the Raman-active radial and tangential vibrational modes of single-wall carbon-nanotube bundles. Using 514.5-nm excitation, we find that the radial mode intensity disappears beyond 1.5 GPa, and the tangential mode intensity also drops considerably above this pressure. This observation is tentatively attributed to a loss in the electronic resonance in the Raman scattering cross section due to a hexagonal distortion in the cylind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

46
435
5

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(486 citation statements)
references
References 22 publications
46
435
5
Order By: Relevance
“…Since then, the radial deformations of the carbon nanotubes in bundles and crystals have been investigated both experimentally and theoretically by many authors. 15,16,[21][22][23][24][25][26][27][28][29] These studies on bundles of SWNTs with particular diameters of ϳ1.4 nm have suggested a pressureinduced phase transformation from circular to either hexagonal or flattened tubes at 1.4-2.1 GPa. 15,[21][22][23][24][25] This shape transition has been indirectly evidenced by the disappearance of symmetric radial breathing modes in Raman spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the radial deformations of the carbon nanotubes in bundles and crystals have been investigated both experimentally and theoretically by many authors. 15,16,[21][22][23][24][25][26][27][28][29] These studies on bundles of SWNTs with particular diameters of ϳ1.4 nm have suggested a pressureinduced phase transformation from circular to either hexagonal or flattened tubes at 1.4-2.1 GPa. 15,[21][22][23][24][25] This shape transition has been indirectly evidenced by the disappearance of symmetric radial breathing modes in Raman spectra.…”
Section: Introductionmentioning
confidence: 99%
“…15,16,[21][22][23][24][25][26][27][28][29] These studies on bundles of SWNTs with particular diameters of ϳ1.4 nm have suggested a pressureinduced phase transformation from circular to either hexagonal or flattened tubes at 1.4-2.1 GPa. 15,[21][22][23][24][25] This shape transition has been indirectly evidenced by the disappearance of symmetric radial breathing modes in Raman spectra. 21,22 The shape transition has also been directly observed in the diffraction experiments, by either x-ray 15,16 or neutron, 27 although there remains inconsistency in these experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 also shows the local environment of the carbon atoms involved in the interbonding of the nanotubes for (6,0) and (7,0). In the first case, the covalent bonding occurs between carbon atoms on two hexagonal rings (Fig.…”
mentioning
confidence: 99%
“…The intertube interactions in nanoropes can be probed by applying external pressure to vary the intertube distance [6][7][8] . For fullerenes, such high pressure studies have yielded many interesting results including new compounds such as the pressure-induced polymeric phases of C 60 9 .…”
mentioning
confidence: 99%
“…10,11 The methanol-ethanol medium is used in several high pressure studies on CNTs. 6,[12][13][14][15][16][17] Argon gas adsorption studies on CNTs 18 identified several adsorption sites: interstitial channels, external groove sites, and the external surface. Pseudohexagonal medium range ordering of adsorbents have been predicted on the external surface of CNTs.…”
mentioning
confidence: 99%